2017
DOI: 10.1016/j.orgel.2017.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Use of gas cluster ion source depth profiling to study the oxidation of fullerene thin films by XPS

Abstract: Use of gas cluster ion source depth profiling to study the oxidation of fullerene thin films by XPS. Organic Electronics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Surface-sensitive techniques such as Secondary Ion Mass Spectrometry (SIMS), X-ray Photoelectron Spectroscopy (XPS), and Auger Electron Spectroscopy (AES) combined with ion-induced material removal can be used to create spatial maps of the chemical composition of materials in a process called depth profiling. This approach has been successfully applied to many systems both inorganic and organic. The main problem of depth profile acquisition is the degradation of resolution with a time of analysis . There are two main factors in play here: topography development , and ion-beam-induced material alteration. ,, The latter issue is virtually solved by the introduction of large gas cluster ion beams (GCIB). The topography development problem can be mitigated by sample rotation .…”
mentioning
confidence: 99%
“…Surface-sensitive techniques such as Secondary Ion Mass Spectrometry (SIMS), X-ray Photoelectron Spectroscopy (XPS), and Auger Electron Spectroscopy (AES) combined with ion-induced material removal can be used to create spatial maps of the chemical composition of materials in a process called depth profiling. This approach has been successfully applied to many systems both inorganic and organic. The main problem of depth profile acquisition is the degradation of resolution with a time of analysis . There are two main factors in play here: topography development , and ion-beam-induced material alteration. ,, The latter issue is virtually solved by the introduction of large gas cluster ion beams (GCIB). The topography development problem can be mitigated by sample rotation .…”
mentioning
confidence: 99%
“…It is important to note that a key ingredient for the aforementioned photodegradation reactions, namely molecular oxygen, was found to diffuse tens of times faster into the interstitial voids in the fullerene lattice when irradiated with UV or visible light. , The presence of oxygen is thus expected to fuel the generation of more singlet oxygen which compounds PS degradation. Using X-ray photoelectron spectroscopy (XPS), we have previously , shown that AM1.5G light exposure leads to the detection of oxidized species in the bulk of PS–PCBM thin films rather than on just the surface in neat PS and neat PCBM films. A similar conclusion can also be reached with FTIR measurements of PS films having various PCBM loadings (0%, 20%, 80%, and 100%).…”
Section: Results and Discussionmentioning
confidence: 99%
“…8,44 The presence of oxygen is thus expected to fuel the generation of more singlet oxygen which compounds PS degradation. Using X-ray photoelectron spectroscopy (XPS), we have previously 19,45 shown that AM1.5G light exposure leads to the detection of oxidized species in the bulk of PS−PCBM thin films rather than on just the surface in neat PS and neat PCBM films. A similar conclusion can also be reached with FTIR measurements of PS films having various PCBM loadings (0%, 20%, 80%, and 100%).…”
Section: Resultsmentioning
confidence: 99%
“…Further analysis of the optimized PCBM layer was carried out using XPS, to determine if any degradation of the surface layer had occurred. This would be expected to be indicated by oxidation of the PCBM molecules and an increase in the oxygen levels detected in the film 50 . Two main O(1s) features due to the ether like and carbonyl oxygen atoms in the ester group of the PCBM side chain are expected to be present in the XPS spectra in the region of 532eV, as was found and is shown in Figure S16.…”
Section: Electron Transport Layer and Inter Layermentioning
confidence: 99%